Three-photon imaging of ovarian cancer - Barton, Jennifer K. (SPIE-INT SOC OPTICAL ENGINEERING, 2016)
Optical imaging methods have the potential to detect ovarian cancer at an early, curable stage. Optical imaging has the disadvantage that high resolution techniques require access to the tissue of interest, but miniature endoscopes that traverse the natural orifice of the reproductive tract, or access the ovaries and fallopian tubes through a small incision in the vagina wall, can provide a minimally-invasive solution. We have imaged both rodent and human ovaries and fallopian tubes with a variety of endoscope-compatible modalities. The recent development of fiber-coupled femtosecond lasers will enable endoscopic multiphoton microscopy (MPM). We demonstrated two-and three-photon excited fluorescence (2PEF, 3PEF), and second-and third-harmonic generation microscopy (SHG, THG) in human ovarian and fallopian tube tissue. A study was undertaken to understand the mechanisms of contrast in these images. Six patients (normal, cystadenoma, and ovarian adenocarcinoma) provided ovarian and fallopian tube biopsies. The tissue was imaged with three-dimensional optical coherence tomography, multiphoton microscopy, and frozen for histological sectioning. Tissue sections were stained with hematoxylin and eosin, Masson's trichrome, and Sudan black. Approximately 1 mu m resolution images were obtained with an excitation source at 1550 nm. 2PEF signal was absent. SHG signal was mainly from collagen. 3PEF and THG signal came from a variety of sources, including a strong signal from fatty connective tissue and red blood cells. Adenocarcinoma was characterized by loss of SHG signal, whereas cystic abnormalities showed strong SHG. There was limited overlap of two-and three-photon signals, suggesting that three-photon imaging can provide additional information for early diagnosis of ovarian cancer.